Translating Public Health Practices: Community-Based Approaches for Addressing Hearing Health Care Disparities - Suen, Jonathan J.; Marrone, Nicole; Han, Hae-Ra; Lin, Frank R.; Nieman, Carrie L. (Seminars in Hearing, 2019)
Epidemiologic studies reveal disparities in hearing health care with lower prevalence of hearing aid use among older adults from racial/ethnic minority groups and lower socioeconomic positions. Recent national reports recommend exploring innovative delivery models to increase the accessibility and affordability of hearing health care, particularly for underserved and vulnerable populations. With an expected rise in the prevalence of age-related hearing loss over the next four decades due to a rapidly aging population, the condition is a growing public health imperative. This review describes key public health practices for developing and delivering community-based care that characterizes an emerging area of research in novel approaches of hearing loss management programs to reach underserved populations. With evolving technologies that enable care to extend beyond the clinic, adapting a long-utilized community health worker approach presents a strategy for the field of hearing health care to be actively involved in designing and leading initiatives for achieving hearing health equity. Principles from community-based participatory research offer a paradigm for the field to integrate into its research endeavors for addressing disparities. An interdisciplinary approach for engaging these challenges offers hearing health care researchers and providers an opportunity to advance the field and delivery of care.
Keywords: hearing health care disparities; age-related hearing loss; community health worker; community-based participatory research